TINGKAT KEPUASAN IBU-IBU RUMAH TANGGA HARAPAN INDAH 2, CLUSTER TAMAN SARI, BEKASI BARAT TERHADAP TAYANGAN THE NEW EAT BULAGA INDONESIA - Nurkhalilla Fajrini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
The New Eat Bulaga Indonesia is a variety show that aired on ANTV which now comes with a much different concept than before that aired on the previous television station, SCTV. The purpose of this research is to determine the magnitude of motives, satisfaction, and the magnitude of differences between motive and satisfaction after watching The New Eat Bulaga Indonesia. The theory was used in this research are Behaviorism, Uses and Gratification theory, and expectancy value theory. The research method used is quantitative with comparative explanative survey. The result of this research is got entertainment motif 3,29 and entertainment satisfaction 3,18, meaning motive (GS) is bigger than satisfaction (GO). That means, the media did not satisfy the audience. The conclusion of this research is The New Eat Bulaga Indonesia did not satisfy the housewives of Harapan Indah 2, Cluster Taman Sari, West Bekasi, especially in RT 005 / RW 009.Â Key words: Watching Motives, Satisfaction of Housewives, The New Eat Bulaga Indonesia.